Extractive purification of recombinant peroxidase isozyme c from insect larvae in aqueous two-phase systems - Targovnik, Alexandra Marisa (2012)
Aqueous two-phase systems (ATPS) have not yet been applied to purify proteins expressed in insect larvae infected by recombinant baculovirus. This work describes the behavior of typical contaminants in the baculovirus-insect larvae expression system such as larval proteins and baculovirus particles in PEG/phosphate ATPSs, in addition to the extraction and purification of the target protein (horseradish peroxidase isozyme C, HRPC). After assessing the influence of PEG molecular weight, system pH and added salt on the partition constants of HRPC and total protein of a clarified larvae extract, two ATPSs were selected for the first extraction step: PEG 1500/phosphate, pH 7.0 with 4.0 % NaCl (System 1) and PEG/phosphate, pH 5.0 in the absence of NaCl (System 2). Both systems were found to be appropriate since a clarified enzyme-enriched top phase was obtained with a yield of 99 and 90 % respectively. The direct partition of larvae homogenized with the components of systems 1 and 2, yielded a HRPC recovery in top phase of 71.4% and 81.1% respectively, whereas total protein recovery was 5.2% and 3.3% respectively. In both systems, the top phase was clear and particulate material remained in the interphase and the bottom phase. The bulk of immunogenic proteins of the larvae concentrated in the bottom phase of both systems. The PCR assay revealed the presence of viral DNA in both phases.             It was possible to extract the HRPC back from the PEG-rich phase by adding a fresh magnesium sulphate solution to form a new ATPS, achieving a recovery in the bottom phase of 50% and 98% in Systems 1 and 2 respectively, whereas the recovery of total protein was 69 % and 24 % respectively. The HRPC global recovery of the two-step processes was 35.4 % and 79.6 % for Systems 1 and 2, with purification factors of 14.5 and 114.2 respectively. The final product was free of viral particles.